Editorial: connecting the dots in fisheries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Are ICTs in the fisheries sector benefiting ACP countries? Recent studies paint an ambiguous picture. While ICTs offer cost-effective mean